Susceptibility of group B streptococci to 16 beta-lactam antibiotics, including new penicillin and cephalosporin derivatives. - Jacobs, M R (1982)
The susceptibility of 100 group B streptococci to 16 beta-lactam antibiotics was tested by agar dilution. Penicillin G and N-formimidoyl thienamycin were the most active agents tested, both having a 90% minimal inhibitory concentration (MIC90) of 0.06 microgram/ml. Ceftriaxone, cefotaxime, cefamandole, and SCH 29482 were almost as active, all having an MIC90 of 0.12 microgram/ml, and ampicillin, cephalothin, and mezlocillin all had an MIC90 of 0.25 microgram/ml. The MIC90 for piperacillin, cefoperazone, and ceftazidime was 0.5 microgram/ml. Least active were carbenicillin, ticarcillin, cefoxitin, and moxalactam, with MIC90s of 1, 2, 4, and 8 micrograms/ml, respectively. No penicillin-tolerant strains were detected.